Microstructure and mechanical property in heat affected zone (HAZ) in F82H jointed with SUS316L by fiber laser welding. (December 2016) - Kano, S.; Oba, A.; Yang, H.L.; Matsukawa, Y.; Satoh, Y.; Serizawa, H.; Sakasegawa, H.; Tanigawa, H.; Abe, H.
Abstract: This study investigates the microstructure and mechanical property in heat affected zone (HAZ) between F82H and SUS316L jointed by 4 kW fiber laser welding at different parameters such as laser scan rate and beam position. OM/FE-SEM observation, EPMA analysis and nano-indentation hardness test were utilized to characterize the microstructure and evaluate the mechanical property. Results show that the HAZ width is dependent on the welding condition. The precipitation of M23 C6 particle in HAZ is found to be closely related to the distance from WM/HAZ interface. Decrease in Cr and C concentration in M23 C6 depended on the welding condition; the decrease was relatively milder in the case of shifting the beam position to SUS side. Furthermore, the rapid increment in nano-indentation hardness, i.e. ≈2500 MPa, at HAZ/F82H interface was observed regardless of welding parameters. The temperatures at HAZ/F82H interface were estimated from Cr and C concentration change of M23 C6 by EPMA. It was revealed that the temperature of HAZ/F82H interface increased with increasing HAZ width, and that the presence of over-tempered HAZ (THAZ) region is confirmed only in the specimens welded right on the F82H/SUS interface (no-shift) at the laser scan rate of 3 m/min.